Comparison of Three Nucleic Acid Amplification Assays of Cerebrospinal Fluid for Diagnosis of Cytomegalovirus Encephalitis - Bestetti, Arabella (American Society for Microbiology, 2001)
The diagnostic reliabilities of three cytomegalovirus (CMV) nucleic acid amplification assays of cerebrospinal fluid (CSF) were compared by using CSF samples from human immunodeficiency virus-infected patients with a postmortem histopathological diagnosis of CMV encephalitis (n = 15) or other central nervous system conditions (n = 16). By using a nested PCR assay, the quantitative COBAS AMPLICOR CMV MONITOR PCR, and the NucliSens CMV pp67 nucleic acid sequence-based amplification assay, sensitivities were 93.3, 86.6, and 93.3%, respectively, and specificities were 93.7, 93.7, and 87.5%, respectively. The COBAS AMPLICOR assay revealed significantly higher CMV DNA levels in patients with diffuse ventriculoencephalitis than in patients with focal periventricular lesions.